2019
DOI: 10.1101/705020
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lorcaserin maintenance fails to attenuate heroin vs. food choice in rhesus monkeys

Abstract: Background:The current opioid crisis has reinvigorated preclinical research in the evaluation of non-opioid candidate treatments for opioid use disorder (OUD). Emerging evidence suggests 5-HT 2C receptor agonists may attenuate the abuse-related effects of opioids. This study evaluated effectiveness of 7-day treatment with the clinically available 5-HT 2C agonist lorcaserin on heroin-vs.-food choice in rhesus monkeys. Lorcaserin effects were compared to effects produced by saline substitution and by 7-day treat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…This extends the range of conditions under which we have observed dose-dependent increases in choice of a drug in comparison to a nondrug alternative reinforcer in a concurrent-choice procedure of drug availability. Second, continuous naltrexone maintenance for 7 days (monkeys) or 5 days (rats) failed to significantly alter amphetamine choice in either species despite assessment of naltrexone doses sufficient to produce >10-fold rightward shifts in opioid choice dose-effect curves in similar choice procedures (Townsend et al, 2019(Townsend et al, , 2020. This finding contrasts with previous evidence to suggest a role for mu opioid receptor (MOR) activation in mediating misuse-related effects of amphetamine.…”
Section: Overviewmentioning
confidence: 59%
See 1 more Smart Citation
“…This extends the range of conditions under which we have observed dose-dependent increases in choice of a drug in comparison to a nondrug alternative reinforcer in a concurrent-choice procedure of drug availability. Second, continuous naltrexone maintenance for 7 days (monkeys) or 5 days (rats) failed to significantly alter amphetamine choice in either species despite assessment of naltrexone doses sufficient to produce >10-fold rightward shifts in opioid choice dose-effect curves in similar choice procedures (Townsend et al, 2019(Townsend et al, , 2020. This finding contrasts with previous evidence to suggest a role for mu opioid receptor (MOR) activation in mediating misuse-related effects of amphetamine.…”
Section: Overviewmentioning
confidence: 59%
“…First, naltrexone was administered by continuous infusion to mimic maintenance conditions used clinically with substance use disorder treatment medications. Naltrexone was delivered by continuous intravenous infusion for 7 days in monkeys and by continuous subcutaneous minipump delivery for 5 days in rats, as we have reported previously in models of treatment for opioid use disorder (Townsend et al, 2019(Townsend et al, , 2020. We hypothesized that naltrexone maintenance would reduce amphetamine choice and increase food choice.…”
mentioning
confidence: 99%
“…Previous preclinical studies using non-choice schedules of reinforcement have demonstrated that opioid self-administration can be attenuated by either selective MOR antagonists (Negus et al 1993;Zernig et al 1997) or genetic MOR deletion (Becker et al 2000;Sora et al 2001). For example, Figure 5 shows effects of the opioid antagonist naltrexone on heroin-vs.-food choice in nondependent rhesus monkeys and fentanyl-vs.-food choice in nondependent rats (Townsend et al 2019a(Townsend et al , 2019c. Specifically, continuous naltrexone infusion produced dose-dependent rightward shifts in the opioid choice dose-effect function (i.e., decreased opioid choice) in both species, and these doses of naltrexone did not reduce the total number of choices completed.…”
Section: Mor Antagonistsmentioning
confidence: 99%
“…For example, G q /G 11 -protein-coupled 5-HT 2C receptors are also located on VTA GABA-ergic neurons, and acute pretreatment with the 5-HT 2C agonist MK-212 blunts morphine-induced increase in nucleus accumbens dopamine levels (Willins and Meltzer 1998). However, chronic treatment with the clinically available 5-HT 2C agonist lorcaserin (Belviq) failed to attenuate heroin-vs.food choice in rhesus monkeys (Townsend et al 2019c). Furthermore, these preclinical results were consistent with lorcaserin effects on oxycodone vs. money choice in humans (Brandt, Jones, Martinez, Manubay, Mogali, Ramey, Levin, and Comer, pers.…”
Section: Mor Agonistsmentioning
confidence: 99%
See 1 more Smart Citation